2014
DOI: 10.1136/bmj.g4081
|View full text |Cite
|
Sign up to set email alerts
|

Dog ownership has unknown risks but known health benefits: we need evidence based policy

Abstract: Politically driven UK legislation that targets “dangerous dogs” has not been shown to reduce dog bites, writes Rachel Orritt, who calls for policy to be based on robust evidence of incidence and risk assessment of ownershi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…With a dog population of around 8.5 million 1 in the UK (ie, 1 for every 7–8 people in a population of 65 million) 2 dog bites are bound to occur. 3 However, the rate of dog bite occurrence remains unknown, 4 which has implications for knowledge of the true burden on public health and economic loss to the health system. There are an estimated 6743 hospital admissions for ‘dog bites and strikes’ per year in England 5 and 9500 for dog bites in USA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…With a dog population of around 8.5 million 1 in the UK (ie, 1 for every 7–8 people in a population of 65 million) 2 dog bites are bound to occur. 3 However, the rate of dog bite occurrence remains unknown, 4 which has implications for knowledge of the true burden on public health and economic loss to the health system. There are an estimated 6743 hospital admissions for ‘dog bites and strikes’ per year in England 5 and 9500 for dog bites in USA.…”
Section: Introductionmentioning
confidence: 99%
“…6 7 However, these figures actually concern ‘bites and strikes’ from a dog (strikes meaning injury caused by a dog but not from a bite), yet are commonly misreported as dog bites. 4 Statistics concerning actual dog bites require clarification. Further, prevalence studies based on hospital admission records do not include likely less serious dog bites which do not require medical treatment or are treated elsewhere, including Accident and Emergency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of these studies have focused on adults, while much less is known about the role of companion animals related to children in the family environment. On one hand, pets are thought to give both physiological and psychological health support, but on the other hand, they can represent a risk as far as bites and zoonosis are concerned [ 7 , 8 ]. A few studies have reported the perceptions of the children themselves about having a pet [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%